Kekerasan dan Kontrol Sosial dalam Film Hellbound Perspektif Semiotika Charles Sanders Peirce - Fadhel Muhammad; Syahrul Rhomadan; Nazhar Maulana (PT. Intelek Cendikiawan Nusantara, 2025)
Film functions as both an artistic medium and a form of communication that reflects and shapes social and ideological dynamics. Hellbound, a South Korean series adapted from a popular webcomic, presents a narrative centered on supernatural violence and social control legitimized through religious belief and authority. This study aims to analyze the representation of violence and social control in Hellbound through the lens of Charles Sanders Peirce’s semiotic theory, which explores the relationship between the sign, object, and interpretant in the construction of meaning. This research employs a qualitative approach with descriptive analysis. Data were collected through literature review and in-depth observation of the film’s narrative and visual elements. The findings reveal that Hellbound utilizes iconic, indexical, and symbolic signs to represent collective fear, ideological power, and the legitimization of violence under religious morality. The character Jung Jinsu and the religious group The New Truth serve as symbolic representations of authoritarian religious authority, while the Arrowhead group reflects the manifestation of organized social violence. The study concludes that Hellbound constructs a complex semiotic system to critique the misuse of religion, ideological domination, and the fragility of society under social control. Peirce’s semiotic theory contributes significantly to understanding the construction of meaning and ideological dynamics within popular media.